Runx2 activates hepatic stellate cells to promote liver fibrosis via transcriptionally regulating Itgav expression - Li Zhong; Jinqiu Zhao; Lu Huang; Yi Liu; Xiaoxiao Pang; Ke Zhan; Shan Li; Qian Xue; Xiaoli Pan; Liang Deng (Clinical and Translational Medicine, 2023)
Abstract Backgrounds and aims As a central event during liver fibrosis, hepatic stellate cells (HSC) have been thought to be a potential therapeutic target for liver fibrosis. Previous studies have shown that runt‐related transcription factor 2 (Runx2) is associated with the development of non‐alcoholic fatty liver disease, while its specific role in HSC activation and hepatic fibrosis remains elusive. Approach and results In this study, we found that Runx2 expression was significantly upregulated in human liver fibrosis with different aetiologies. Runx2 expression was also gradually elevated in mouse liver during fibrosis, and Runx2 was mainly expressed in the activated HSC. Knockdown of Runx2 in HSC markedly alleviated CCl4‐induced, 3,5‐diethoxycarbonyl‐1,4‐dihydrocollidine‐induced or methionine‐choline deficient (MCD)‐induced liver fibrosis, while hepatic overexpression of Runx2 via HBAAV‐Runx2 or VA‐Lip‐Runx2 injection exacerbated CCl4‐induced liver fibrosis. In vitro analysis demonstrated that Runx2 promoted HSC activation and proliferation, whereas Runx2 knockdown in HSC suppressed these effects. RNA‐seq and Runx2 ChIP‐seq analysis demonstrated that Runx2 could promote integrin alpha‐V (Itgav) expression by binding to its promoter. Blockade of Itgav attenuated Runx2‐induced HSC activation and liver fibrosis. Additionally, we found that cytokines (TGF‐β1, PDGF, EGF) promote the expression and nuclear translocation of Runx2 through protein kinase A (PKA) in HSC. Conclusions Runx2 is critical for HSC activation via transcriptionally regulating Itgav expression during liver fibrosis, and may be a promising therapeutic target for liver fibrosis.